A mechanism for ageing in a deeply supercooled molecular glass. Issue 52 (9th June 2021) - Cassidy, Andrew; Jørgensen, Mads R. V.; Glavic, Artur; Lauter, Valeria; Plekan, Oksana; Field, David
Abstract : A molecular glass spontaneously polarises upon growth. The temporal decay of this polarization is directly related to the rotation of molecular dipoles and we use this to track an ageing pathway in a deeply supercooled glassy solid. Abstract : Measurements of the decay of electric fields, formed spontaneously within vapour-deposited films of cis -methyl formate, provide the first direct assessment of the energy barrier to secondary relaxation in a molecular glass. At temperatures far below the glass transition temperature, the mechanism of relaxation is shown to be through hindered molecular rotation. Magnetically-polarised neutron scattering experiments exclude diffusion, which is demonstrated to take place only close to the glass transition temperature.